Sarcopenia is a Predictor for Adverse Clinical Outcome in Pediatric Inflammatory Bowel Disease. Issue 6 (June 2021) - Atlan, Lilian; Cohen, Shlomi; Shiran, Shelly; Sira, Liat Ben; Pratt, Li-Tal; Yerushalmy-Feler, Anat
ABSTRACT: Objectives: Inflammatory bowel disease (IBD) has a high impact on nutritional status. Sarcopenia is related to higher risk of surgery and rescue therapy in adults with IBD; however, comparable data in pediatric populations are scarce. We evaluated muscle mass as a predictor of disease outcome in pediatric IBD. Methods: All pediatric IBD patients who underwent magnetic resonance enterography (MRE) during 2008 to 2019 were included. Muscle mass was assessed by measuring the area of the psoas muscle at the upper level of L3 on MRE. The psoas area divided by the body surface area (BSA) yielded the psoas index. Clinical and radiological data, including disease location, activity, course, and medications were documented. The control group included non-IBD children who underwent an MR imaging study. Results: We enrolled 101 IBD patients, 69 (68.3%) with Crohn disease (CD) and 32 (31.7%) with ulcerative colitis (UC) (mean age 15.03 ± 3.27 years). The psoas index was significantly lower in the IBD patients compared with the 87 controls (326 vs 528, respectively, P  < 0.001). Patients with a psoas index in the lowest quartile had significantly higher risk for biologic therapy (multivariate analysis, hazard ratio [HR] = 12.1, P  = 0.046) and disease exacerbation (HR = 9, P  = 0.047) independently of body mass index, compared with patients with a psoas index in the uppermost quartile. Conclusions: Sarcopenia correlates with the radiological severity of pediatric IBD and serves as a predictor for adverse clinical disease outcome. Muscle mass measurement in MRE studies may serve as a possible marker for disease outcome in this population. Abstract : Supplemental Digital Content is available in the text